Human vs Machine: A Comparative Effectiveness of A Particular Technique and AI Tools in Improving Writing Skills - Delfia Herwanis; Rahmanita Zakaria; Rusmiati Rusmiati; Sungkawati Sukardi Wahyuningsih (Ta'dib, 2024)
The research paper titled "Human vs. Machine: A Comparative Effectiveness of A Particular Technique and Artificial Intelligence Tools in Improving Writing Skills." The study investigates the efficacy of a certain method and artificial intelligence tools in improving students' English writing proficiency. The goal of this research is to provide information that will contribute to the development of writing training programs that are both effective and tailored to individual needs. This will ensure a comprehensive approach to language acquisition in the modern age of technology. The study utilized a combination of quantitative and qualitative methodologies to assess the influence of these tools on students' writing abilities. The results emphasize the significance of customized writing instruction that integrates both technological and pedagogical elements in order to improve students' writing skills.